Implementation of Salam Contracts in the Sharia Principles Framework: Surveys and Prospects in the Field - Valijon Ghafurjonovich Macsudov; Aliem Amsalu; João Souza-Junior; Nawwal Tattaqillah (Walidem Institute and Publishing (WIP), 2024)
This study aims to explore the implementation of the salam contract in the view of Sharia and analyze its prospects in the context of practice in the field. The research method used was a survey study involving participants consisting of religious experts, Islamic finance practitioners, and the general public. Data was collected through questionnaires and interviews to gain a comprehensive understanding of their views on the greeting contract. A qualitative analysis was conducted to understand the implications of sharia and the practical prospects of implementing the salam contract. The results showed that the Salam contract can be implemented by taking into account relevant sharia principles, such as fairness and clear legal provisions. However, challenges may arise regarding uniform understanding and the need for appropriate regulation to facilitate widespread practice in the field. The prospect of implementing the contract of greetings in financial and trade transactions promises more inclusive and sustainable economic sustainability under Sharia principles. This research provides a deeper understanding of the relevance and potential of the salam contract in the context of Islamic economics and provides a foundation for further development in its practice in the field.